A TRIPS-Covid waiver and overlapping commitments to protect intellectual property rights under international IP and investment agreements - Henning Große Ruse-Khan; Federica Paddeu (South Centre, 2022)
This paper considers legal implications that are likely to emerge from the implementation of a TRIPS Waiver decision. Assuming that a Waiver is adopted in the form presented in the May 2021 proposal by South Africa and India et al, we review the interaction between the Waiver and other commitments to protect IP rights under international IP and investment treaties. Our principal research question is to analyze whether domestic measures implementing the Waiver are compatible with the implementing State's other obligations to protect IP rights established under multilateral IP treaties, IP and Investment Chapters of FTAs as well as BITs. In light of typical examples for such overlapping commitments, we first focus on (1) defences directly affecting compatibility with these treaty commitments (here referred to as 'internal' defences). In a second part, we review (2) potential defences under general international law that may serve to justify (in other words, to preclude the wrongfulness of) such measures. We conclude that often internal and/or general defences will operate to support the implementation of the Waiver despite overlapping commitments in international IP and investment law. This conclusion is reinforced by a purpose-oriented understanding of the TRIPS Waiver as authorizing measures necessary to achieve the goal of 'unimpeded, timely and secure access' for all to covered medical technologies 'for the prevention, treatment or containment of COVID-19'.
Keywords: 300; Immaterialgüterrechte; Internationales Investitionsrecht; TRIPS; Internationale Handelspolitik; Welt